EXPERIMENTAL STUDY ON VITRIFICATION OF CRYOPROTECTANTS USING THIN-FILM EVAPORATION OF NITROGEN - Roth Vidaletti, Henrique; Renan Stochero Da Silva, Alisson; Biancon Copetti, Jacqueline; Henrique Macagnan, Mario; Dichi De Oliveira, Jeferson; Maria Cardoso, Elaine; Manetti, Leonardo (Revista de Engenharia Térmica, 2024)
Nitrogen thin film evaporation is a novel technique applied to cryopreservation, which aims to improve the preservation of biological samples at ultra-low temperatures. Cryopreservation is a critical process used in various fields, including biomedical research, regenerative medicine, and the storage of genetic materials. Traditional cryopreservation methods often suffer from sample damage caused by ice crystal formation and chemical toxicity associated with conventional cryoprotectants. This study developed an experimental apparatus comprising a vacuum chamber and two cryocauteries. The sample is stored in a polydimethylsiloxane-based composite reservoir between two copper plates with a nickel microporous outer surface. This system is suspended inside the chamber, and nitrogen jets promote evaporation. Chamber pressure and sample temperatures are recorded during the experiments. Tests were performed using dimethyl sulfoxide, glycerol and sucrose solutions in phosphate-buffered saline at different concentrations and volumes to evaluate vitrification and cooling rates. Effects of volume and concentration were evaluated, and it was found that vitrification success is directly related to the cryoprotective agent concentration used. In addition, no significant impact on the visual appearance of the samples related to vitrification regarding the sample geometry was observed. The copper foam porous surface resulted in the highest cooling rate, which is associated with the properties of the foam, such as its high thermal conductivity.